1997
DOI: 10.1038/sj.ijo.0800457
|View full text |Cite
|
Sign up to set email alerts
|

Is an ephedrine caffeine treatment contraindicated in hypertension?

Abstract: OBJECTIVES: To examine how the slimming drug, Letigen 1 , containing ephedrine (E) 20 mg and caffeine (C) 200 mg (E C), affects blood pressure in normotensive and hypertensive patients treated with adrenergic b-receptor blocking drugs and/or other antihypertensive agents, during a period of six weeks. DESIGN: A double-blind, randomised, placebo controlled study of ®ve parallel groups of overweight patients from general practices. SUBJECTS: One hundred and thirty-six patients with Body Mass Index (BMI) b 25 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The pharmacological properties and physiological effects of ephedrine, [8][9][10][11] of (+)-and (±)-norephedrine 12 and of pseudoephedrine 13 have been studied.…”
Section: Cephalotaxine and Related Alkaloids 21mentioning
confidence: 99%
“…The pharmacological properties and physiological effects of ephedrine, [8][9][10][11] of (+)-and (±)-norephedrine 12 and of pseudoephedrine 13 have been studied.…”
Section: Cephalotaxine and Related Alkaloids 21mentioning
confidence: 99%
“…It also increases metabolism and suppresses appetite, thus promoting body fat decomposition [12,13]. Several studies have shown that single or mixed preparations of ephedrine can lead to weight loss and increased energy [14][15][16][17]. According to Douglas et al, patients taking ephedrine-containing capsules had a greater weight loss than those taking placebo (−3.1 kg vs. −2.1 kg in 8 weeks) [15].…”
Section: Introductionmentioning
confidence: 99%